Determination of diffusion coefficient of a miscible CO2/n-hexadecane system with Dynamic Pendant Drop Volume Analysis (DPDVA) technique. (August 2019) - Du, Dongxing; Zheng, Lichen; Ma, Kaiyang; Wang, Fei; Sun, Zhifeng; Li, Yingge
Highlights: A simplified mass transfer model adapted to the oil-gas miscibility condition is proposed. The experimental technique and operation details are comprehensively described. For the first time, the diffusion coefficients of a miscible CO2 /n-hexadecane system are reported. Abstract: A clear understanding of the diffusion characteristics between oil and CO2 phase in the miscible front is substantial to operate a successful CO2 miscible flooding process. However, there are few studies on diffusion characteristics of CO2 /hydrocarbon systems under the multi-contact miscible state. In this paper, the Dynamic Pendant Drop Volume Analysis (DPDVA) technique is employed to obtain the diffusion coefficients of the CO2 /n-hexadecane system over the Minimum Miscibility Pressure (MMP) conditions. Based on the oil droplet volume variation histories, a simplified mass transfer model adapted to the oil-gas miscibility condition is proposed. For the first time, the diffusion coefficients of a miscible CO2 /n-hexadecane system at temperature range of 26.9–79.6 °C and the pressure range of 7–19 MPa were measured. It is found the diffusion coefficients close to the MMP condition have the same magnitude values compared to the literature reported results in immiscible conditions, indicating a nearly stable diffusion rate before system miscibility and in the meantime validating the experimental technique employed in this paper. On the other hand, larger diffusion coefficient appears under lower temperature and higher pressure conditions under miscible conditions, and a clearly linear relationship is observed between the diffusion coefficient and the system pressure. It is expected the study can fill some gaps in the research field of oil/gas miscible diffusion characteristics and help optimize the gas injection miscible flooding processes.